2016
DOI: 10.1007/s00105-016-3831-1
|View full text |Cite
|
Sign up to set email alerts
|

Trichophyton violaceum

Abstract: The anthropophilic dermatophyte T. violaceum represents the most frequent cause of tinea capitis in western Uganda. For successful management oral antifungal therapy is necessary together with supportive topical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Africa, other Trichophyton species like T. Verrucosum and T. violaceum are the more common causes of tinea capitis than T. tonsurans 20 . A study done in Uganda based on 115 patients aged 1–16 years, reported T. violaceum (56.6%) as the most common cause of tinea capitis followed by Microsporum audouinii (13%) 24 . Unlike the general geographic distribution of the species reported before, Trichophyton genera were the predominant species of dermatophyte isolated from hair/scalp samples in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, other Trichophyton species like T. Verrucosum and T. violaceum are the more common causes of tinea capitis than T. tonsurans 20 . A study done in Uganda based on 115 patients aged 1–16 years, reported T. violaceum (56.6%) as the most common cause of tinea capitis followed by Microsporum audouinii (13%) 24 . Unlike the general geographic distribution of the species reported before, Trichophyton genera were the predominant species of dermatophyte isolated from hair/scalp samples in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of globalization, not only the aforementioned pathogens occur in Germany, but also cases of dermatophytoses due to T. soudanense and M. audouinii , which are preferentially found in West Africa, have been described in the past 3–6 . To the best of our knowledge, the occurrence of mixed tinea capitis infections have been reported from involved patients in Uganda but have not been described in Germany in the literature so far 7,8 …”
Section: Introductionmentioning
confidence: 94%
“…[3][4][5][6] To the best of our knowledge, the occurrence of mixed tinea capitis infections have been reported from involved patients in Uganda but have not been described in Germany in the literature so far. 7,8…”
Section: Introductionmentioning
confidence: 99%